Analisis Tingkat Kecemasan Pada Pasien Systemic Lupus Erythematosus (SLE) Di Komunitas Odapus Lampung Pada Masa Pandemi Covid-19 - Rina Kriswiastiny; Festy Ladyani Mustofa; Firhat Esfandiari; Jane Elvina (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Systemic lupus erythematosus (SLE) is an autoimmune disease that attacks the immune system. Patients with SLE who are immunologically and genetically compromised are predisposed to infection. Currently the world, including Indonesia, is being hit by the COVID-19 pandemic, which is a respiratory tract infection caused by the corona virus. Because of the easy and fast way of transmission, the community is no exception for SLE sufferers who are more susceptible to infection for fear of contracting this virus, this can cause psychological conditions that can be experienced, namely anxiety. To determine the analysis of anxiety levels in patients with Systemic Lupus Erythematosus Community ODAPUS Lampung during the COVID-19 Pandemic. This type of research is descriptive with a cross sectional approach using the Zung Self-rating Anxiety Scale online questionnaire. The sample of this study was all patients diagnosed with Systemic Lupus Erythematosus in the ODAPUS Lampung community as many as 40 people. Data analysis used univariate analysis by using tables in presenting the data. The results of the study of 40 patients showed that the characteristics of SLE patients based on age were mostly adults (65%), the most gender were women (97.5%), the last education was college. (60%), most of the jobs are at university level. IRT (42.5%), on the level of anxiety obtained normal anxiety (50%) and mild anxiety (50%). It is known that the analysis of the level of anxiety in patients with Systemic Lupus Erythematosus Community ODAPUS Lampung during the COVID-19 pandemic showed that there were 20 patients with normal anxiety levels, 20 patients with mild anxiety, and no patients with mild anxiety. moderate or severe anxiety levels of a total of 40 patients. Keywords: SLE, COVID-19, Anxiety Level  ABSTRAK Systemic lupus erythematosus (SLE) adalah suatu penyakit autoimun, yang menyerang kekebalan tubuh. Pasien dengan SLE yang terganggu imunologi serta genetik menjadi predisposisi terjadinya infeksi. Saat ini, dunia termasuk Indonesia sedang dilanda pandemi COVID-19 yang merupakan infeksi saluran pernapasan oleh corona virus. Karena cara penularannya yang mudah dan cepat membuat masyarakat tidak terkecuali pasien SLE yang lebih rentan terkena infeksi takut tertular oleh virus ini, hal ini dapat menyebabkan satu keadaan psikologi yang bisa dialami yaitu rasa cemas. Tujuan penelitian ini untuk mengetahui Analisis Tingkat Kecemasan pada pasien Systemic Lupus Erythematosus di Komunitas ODAPUS Lampung pada masa Pandemi COVID-19. Jenis penelitian ini adalah deskriptif dengan pendekatan Cross-sectional menggunakan kuesioner Zung Self-rating Anxiety Scale secara online. Sampel penelitian ini adalah seluruh pasien yang terdiagnosa Systemic Lupus Erythematosus di komunitas ODAPUS Lampung sebanyak 40 orang. Analisis data menggunakan analisis univariat dengan menggunakan tabel dalam penyajian data. Hasil penelitian dari 40 pasien tersebut didapatkan karakteristik pasien SLE berdasarkan usia terbanyak yaitu pada dewasa (65%), jenis kelamin terbanyak yaitu perempuan (97,5%), pendidikan terakhir terbanyak pada tingkat perguruan tinggi (60%), pekerjaan terbanyak pada IRT (42,5%), pada tingkat kecemasan didapatkan normal (50%) dan kecemasan ringan (50%). Diketahui analisis tingkat kecemasan pada pasien Systemic Lupus Erythematosus di Komunitas ODAPUS Lampung pada masa pandemi COVID-19 yaitu didapatkan tingkat kecemasan normal terdapat 20 pasien, kecemasan ringan 20 pasien dan tidak ditemukan pasien pada tingkat kecemasan sedang maupun berat dari total keseluruhan 40 pasien. Kata Kunci : SLE, COVID-19, Tingkat Kecemasan